Analysis of Free Fatty Acid in Rheum tanguticum by HPLC-FLD with Pre-Column Derivatization - Sun, Sheng-Nan; Sun, Jing; Peng, Min; Lu, Xue-Feng; Zhou, Yu-Bi; She, Li-Ping; Zhao, Qing-Shuai; You, Jin-Mao; Ye, Run-Rong (Asian Journal of Chemistry, 2014)
Rheum tanguticum Maxim. ex Balf. is a famous traditional Chinese medicinal herb used in conditions including constipation and inflammation. Chemical compounds in Rh. tanguticum have been studied widely, but to date the free fatty acids have not been analyzed. In the present study, free fatty acids present in Rh. tanguticum were detected using a high-performance liquid chromatography fluorescence detection (HPLC-FLD) method coupled with pre-column derivatization. The labeling reagent 2-(5-benzoacridine)ethyl-p-toluenesulfonate (BAETS) was used to derivatize with free fatty acids and the derivatives were separated on HPLC with gradient elution. This method showed high sensitivity, good stability and repeatability and was applied to the quantitative analysis of free fatty acids in Rh. tanguticum from different regions of Qinghai province. Fifteen saturated fatty acids and four unsaturated fatty acids were detected in these samples. The total content of free fatty acids ranged from 721.08 to 1105.14 μg g-1. Hexadecanoic acid had the highest concentration (average 266.33 μg g-1) and decoic acid the lowest (average 4.59 μg g-1). Four unsaturated fatty acids, including oleic acid, linoleic acid, linolenic acid and hexadecenoic acid were found in Rh. tanguticum, with the ratios unsaturated fatty acids: total fatty acids of 31.47 to 47.25 %. The composition of free fatty acids Rh. tanguticum in are presented in this paper and these results may be useful for the consideration of the nutritional and medical potential of this species.